2004
DOI: 10.1103/physrevb.69.155422
|View full text |Cite
|
Sign up to set email alerts
|

Structure and magnetic properties of adatoms on carbon nanotubes

Abstract: We use ab initio methods to calculate the physical and electronic properties of carbon adatoms on different characteristic carbon nanotubes. We found that for every tube the energetically favored adsorption geometry is a ''bridgelike'' structure between two surface carbons, perpendicular to the long axis of the tube. For adsorption perpendicular or parallel to the axis, the calculations show that the adatom is spin polarized, although the magnitude of the magnetic moment depends mainly on the electronic struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 34 publications
4
50
2
Order By: Relevance
“…While the origin of magnetic ordering in such systems is yet to be fully understood, it has been suggested that spin polarization may arise from local structural defects, 33,36,41,53 sterically protected carbon radicals 34 and chemical impurities. 30,40,43 A unique mechanism for spin ordering in graphene based systems is related to the appearance of edge states. [18][19][20][21][22][23][24][25][26][27][28][29]42,[45][46][47][48][49][50][51][52] When cutting a graphene sheet along its zigzag axis to form a narrow and elongated graphene nanoribbon (GNR), distinct electronic states appear, which are localized around the exposed edges.…”
Section: Introductionmentioning
confidence: 99%
“…While the origin of magnetic ordering in such systems is yet to be fully understood, it has been suggested that spin polarization may arise from local structural defects, 33,36,41,53 sterically protected carbon radicals 34 and chemical impurities. 30,40,43 A unique mechanism for spin ordering in graphene based systems is related to the appearance of edge states. [18][19][20][21][22][23][24][25][26][27][28][29]42,[45][46][47][48][49][50][51][52] When cutting a graphene sheet along its zigzag axis to form a narrow and elongated graphene nanoribbon (GNR), distinct electronic states appear, which are localized around the exposed edges.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier simulations showed that CA and some other defects in nanotubes and other carbon nanomaterials 95,96 can have local magnetic moments. Although the standard STM with the tip made from a nonmagnetic material probes simultaneously the LDOS corresponding to majority and minority spins, an account for magnetism can change the positions of defect-induced peaks.…”
Section: G Spin-polarized Calculationsmentioning
confidence: 99%
“…[24][25][26] They predicted that carbon atoms adsorbed to ͑n ϫ n͒ supercell for n = 5, 6 and 7 generates a magnetic moment of ϳ0.5 B . However, our study for n =2-9 demonstrates that the magnetic moment as well as P vary with n up to n = 9.…”
Section: B Electronic Structurementioning
confidence: 99%